[(6x - 72) : 2 - 84]. 28 = 5628
=> (6x - 72) : 2 - 84 = 5628 : 28 = 201
=> (6x - 72) : 2 = 201 + 84 = 285
=> 6x - 72 = 285 . 2 = 570
=> 6x = 570 + 72 = 642
=> x = 642 : 6
=> x = 107
\(120+\left(56-2x\right).3=156\)
\(\left(56-2x\right).3=156-120\)
\(\left(56-2x\right).3=36\)
\(56-2x=36:3\)
\(56-2x=12\)
\(2x=56-12\)
\(2x=44\)
\(x=44:2\)
\(x=22\)
\(\text{Tìm }x\text{ : }\)
\(a,\text{ }120+\left(56-2x\right)\cdot3=156\)
\(120+168-6x=156\)
\(288-6x=156\)
\(6x=288-156\)
\(6x=132\)
\(x=132\text{ : }6\)
\(x=22\)
\(b,\text{ }3x-2^3=3^2+1^{21}\)
\(c,\text{ }\left\{\left(6x-72\right)\text{ : }2-84\right\}28=5628\)
\(\left(3x-36-84\right)28=5628\)
\(\left(3x-120\right)28=5628\)
\(3x-120=5628\text{ : }28\)
\(3x-120=201\)
\(3x=201-120\)
\(3x=81\)
\(x=81\text{ : }3\)
\(x=27\)